2016
DOI: 10.1111/ijpo.12180
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean birth is not associated with early childhood body mass index

Abstract: SummaryCesarean birth leads to a markedly different microbiome compared to vaginal birth, and the microbiome has been implicated in childhood obesity. Among mothers who had a previous cesarean, we compared anthropometry of 3-to 6-year-old children who were subsequently born by cesarean section versus vaginal birth. This large population-based study involved linking de-identified administrative perinatal and anthropometric data. Children's weight and height were collected at community-based clinics and converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 12 publications
1
30
0
1
Order By: Relevance
“…Three of the included studies were based on populations in Sweden, 31,34,37 two each in America, 35,38 Australia 29,36 and Brazil 32,33 and one in Scotland 30 . The remaining study 40 used data from five underlying datasets from Australia, Canada and America; one of which was the Collaborative Perinatal Project which was also used by one of the other studies 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the included studies were based on populations in Sweden, 31,34,37 two each in America, 35,38 Australia 29,36 and Brazil 32,33 and one in Scotland 30 . The remaining study 40 used data from five underlying datasets from Australia, Canada and America; one of which was the Collaborative Perinatal Project which was also used by one of the other studies 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining study 40 used data from five underlying datasets from Australia, Canada and America; one of which was the Collaborative Perinatal Project which was also used by one of the other studies 35 . Three studies included maternal interpregnancy weight change as the exposure, 29,30,37 three examined maternal smoking status, 30,34,40 two considered mode of birth 36,38 and four the length of the interpregnancy interval 31–33,35 . Further study characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal: short breastfeeding [44], rapid weight gain in the first year of life [45], excess protein intake [5,46], vitamin D deficiency [47,48], and caesarean section (where there is evidence for and against) [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies also reported inconsistent results. Some studies observed a positive relationship between the delivery mode and offspring weight status [ 20 , 21 ], whereas others found no association [ 22 , 23 ]. Therefore, it remains unclear whether the delivery mode independently predicts the occurrence of obesity in later life.…”
Section: Introductionmentioning
confidence: 99%